Intra- and Interspecies Regulation of Gene Expression by Actinobacillus actinomycetemcomitans LuxS - Fong, Karen P. (American Society for Microbiology, 2001)
The cell density-dependent control of gene expression is employed by many bacteria for regulating a variety of physiological functions, including the generation of bioluminescence, sporulation, formation of biofilms, and the expression of virulence factors. Although periodontal organisms do not appear to secrete acyl-homoserine lactone signals, several species, e.g., Porphyromonas gingivalis, Prevotella intermedia, and Fusobacterium nucleatum, have recently been shown to secrete a signal related to the autoinducer II (AI-2) of the signal system 2 pathway in Vibrio harveyi. Here, we report that the periodontal pathogen Actinobacillus actinomycetemcomitans expresses a homolog of V. harveyi luxS and secretes an AI-2-like signal. Cell-free conditioned medium from A. actinomycetemcomitans or from a recombinant Escherichia coli strain (E. coli AIS) expressing A. actinomycetemcomitans luxS induced luminescence in V. harveyi BB170 >200-fold over controls. AI-2 levels peaked in mid-exponential-phase cultures of A. actinomycetemcomitans and were significantly reduced in late-log- and stationary-phase cultures. Incubation of early-log-phase A. actinomycetemcomitans cells with conditioned medium from A. actinomycetemcomitans or from E. coli AIS resulted in a threefold induction of leukotoxic activity and a concomitant increase in leukotoxin polypeptide. In contrast, no increase in leukotoxin expression occurred when cells were exposed to sterile medium or to conditioned broth from E. coli AIS(−), a recombinant strain in which luxS was insertionally inactivated. A. actinomycetemcomitans AI-2 also induced expression of afuA, encoding a periplasmic iron transport protein, approximately eightfold, suggesting that LuxS-dependent signaling may play a role in the regulation of iron acquisition by A. actinomycetemcomitans. Finally, A. actinomycetemcomitans AI-2 added in trans complemented a luxS knockout mutation in P. gingivalis by modulating the expression of the luxS-regulated genes uvrB and hasF in this organism. Together, these results suggest that LuxS-dependent signaling may modulate aspects of virulence and the uptake of iron by A. actinomycetemcomitans and induce responses in other periodontal organisms in mixed-species oral biofilm.